Featured Cover. Issue 7 (15th June 2022) - Zhang, Baoqiang; Zhang, Fanghong; Luo, Huageng
Abstract : The cover image is based on the Research Article Virtual shaft‐based synchronous analysis for bearing damage detection and its application in wind turbines by Baoqiang Zhang et al., https://doi.org/10.1002/we.2727 .